The Impact Of Just In Time Purchase System Implementation In Inventory Cost Efficiency.: Case Study On CV. Prima Jaya In Sidoarjo - I Gede Wiyasa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development in the business world with sharp competition makes companies have to think more or review their business strategies. Improvements in all areas are very important in the development of today's business world, such as increasing productivity, efficiency and service, all of which have become the key to increasing company excellence. To increase efficiency in purchasing activities can be achieved in many ways, one of which is the Just In Time purchasing system. Just In Time is a method that is essentially to reduce waste through purchases in the right amount and time supported by the best quality. According to the results of the discussion that has been carried out, it can be concluded that the factors contained in the Just In Time purchasing system can be applied at CV Prima Jaya because its application can make inventory costs more efficient. In addition, there were also obstacles to quantity, quality, and suppliers. All of that can be overcome by maintaining good relations with suppliers. The implementation of this Just In Time purchasing system cannot be done directly but must be gradual.